In Silico Activity Identification of Cyclo Peptide Alkaloids from Zizyphus Spina-Christi Species Against Sars-Cov-2 Main Protease - Fakih, Taufik Muhammad; Ramadhan, Dwi Syah Fitra; Darusman, Fitrianti (Jurnal Biodjati, 2021)
The COVID-19 has spread worldwide and become an international pandemic. The promising target for drug discovery of COVID-19 was SARS-CoV-2 Main Protease (Mpro), that has been successfully crystallized along with its inhibitor. The discovery of peptide-based inhibitors may present better options than small molecules for inhibitor SARS-CoV-2 Mpro. Natural compounds have such a wide potential and still few explored, Zizyphus spina-christi is one of the medicinal plants that have many pharmacological activities and contains a peptide compound from alkaloids class, i.e. cyclopeptide alkaloids, that is interesting to explore as SARS-CoV-2 Mpro inhibitor. The compound structure was drawn and optimized using density functional theory 3-21G method. The protein chosen was the high resolution of SARS-CoV-2 MPro receptor (1.45 Å) with PDB ID: 6WNP, in complex with boceprevir. Molecular docking simulation was performed using Autodock4 with 100 numbers of GA run, the validation methods assessed by RMSD calculation. Furthermore, the prediction of pharmacological activity spectra was carried out using the PASS Prediction server. The results showed RMSD value was 1.98 Å, this docking method was valid. The binding energy of all compounds showed better results than the native ligand (Boceprevir). The in silico PASS prediction results indicated that all compounds showed antiviral activity. Some compounds showed protease inhibitory activity, i.e Ambiphibine-H, Franganine, and Mauritine-A, and the highest Pa (Predicted activity) value showed by Mauritine-A compounds. It can be concluded that the cyclopeptide compounds of Zizyphus spina-christi were indicated to have a potential as COVID-19 therapy targeting SARS-CoV-2 Mpro.